Climate change and parliamentarians - Ondhowe, Robert (2016)
Argues that although the COP21 Agreement does not include specific reduction targets, its intention was to harness and focus poltical will towards a common solution to the challenges of climate change. States that it is pivotal for creating a platform for global cooperation on climate change.